Population dynamics of notopterus notopterus (Pallas, 1769) from the Kaptai reservoir of Bangladesh (SAARC Journal of Agriculture, 2015)
Population parameters of Notopterus notopterus (Pallas, 1769) from length-frequency data collected from Kaptai Reservoir of Rangamati, Bangladesh from January, 2013 to December, 2013 were calculated by using FiSAT software. The asymptotic total length (L?) and growth coefficient (K) were estimated to be 34.91cm and 0.38 y?1respectively. The instantaneous rate of natural mortality (M), fishing mortality (F) and total mortality (Z) were estimated to be as 0.91 y?1, 0.28 y?1and 1.19 y?1 respectively. The value of exploitation rate (E) was found to be 0.24 which clearly pointed toward moderate or less fishing pressure (E